Leprosy in children in Cuba: Epidemiological and clinical description of 50 cases from 2012-2019 - Raisa Rumbaut Castillo; Laura C. Hurtado Gascón; Jenny Laura Ruiz-Fuentes; Fernanda M. Pastrana Fundora; César R. Ramírez Albajés; Andres F. Henao-Martínez; Carlos Franco-Paredes; Ángel Arturo Escobedo (Public Library of Science (PLoS), 2021)
Introduction In 1993, Cuba achieved leprosy elimination according to the World Health Organization's (WHO) indicator of less than one case per 10,000 population. Despite this achievement, detection of new cases occurs every year among all age groups including children. Detection of new cases in children reveals persistent transmission of the infection. Objective To describe the clinical and epidemiological features of leprosy in individuals younger than 15 years (childhood leprosy) reported to the Cuban National Leprosy Control Program (NLCP) between 2012 and 2019. Methods We conducted a retrospective descriptive study between 2012 and 2019 to assess the clinical and epidemiologic features of individuals under the age of 15 years with a confirmed diagnosis of leprosy reported to the NLCP. We reviewed the NLCP database and collected data to better define the total number of cases of leprosy in adults, children (younger than 15 years). We assessed socio-demographic variables (age, gender, and province of residence) as well as variables of clinical interest including operational classification and staging at diagnosis, bacillary index, grade of disability by WHO staging. Additionally, we evaluated epidemiological variables including passive versus active surveillance of cases, contact investigation focusing specifically in household transmission, and the degree of kinship as well as standing of the child within the focus of transmission when there were additional cases. Results We identified fifty children during the study period corresponding to 3% of the overall cases of leprosy comprising all age groups in Cuba. In the age group younger than 15 years, the majorities of cases was from the Granma province and most were between the ages of 10 and 14 years. Clinically, multibacillary/lepromatous forms were the most common type identified with positive bacillary index. The majority of children diagnosed with leprosy during our study period had a history of a relative with a confirmed diagnosis of leprosy. Conclusions Detection of cases of leprosy in individuals younger than 15 years of age in Cuba demonstrates ongoing transmission of M. leprae in specific geographic hotspots. Its frequency in the early adolescence, the predominant clinical forms, and the mode of detection associated with sources of suspected familiar infection demonstrated that there is a need for further efforts by the NLCP to conduct active surveillance activities among affected communities to identify cases of leprosy earlier with the goal of preventing further household and community transmission. Author summary Leprosy is a chronic mycobacterial infection that affects the skin and peripheral nerves. Despite the wide deployment of effective anti-mycobacterial therapy for this infection, there are still approximately 200,000 new cases of leprosy identified every year globally. The WHO leprosy elimination strategy reduced the overall prevalence of the disease, but the detection of new cases indicates ongoing transmission in many countries. The detection of cases of leprosy in children is a surrogate marker of ongoing transmission in the community. In this study conducted in Cuba, we identified that the Cuban National Leprosy Control Program (NLCP) continues to see an important number of cases of leprosy in children (under the age of 15 years) in selected communities in many of the Cuban provinces. Additionally, we observed that in most cases either one or more relatives with leprosy residing in the same household. In summary, our study highlights to achieve interrupting of leprosy transmission in Cuba; there is a need for further active surveillance efforts targeting selected provinces and communities to identify cases early in their clinical course and institute antimicrobial therapy. Contact investigation is one of the main tools to achieve interruption of transmission.